Using Blended Learning - Hew, Khe Foon. author. aut Link
VII, 120 p. 20 illus.
Keywords: This book discusses evidence-based practices related to the use of blended learning in both K-12 and higher education settings. Specifically, this book features evidence-based practices in relation to the following five learning goals: (a) Fostering students’ attitude change toward country, (b) Helping students’ solve ill-structured design task problems, (c) Improving students’ critical thinking in assessing sources of information, (d) Improving students’ narrative and argumentative writing abilities and (e) Enhancing students’ knowledge retention and understanding. To achieve this aim, the authors draw upon their own research studies as well as some other relevant studies to reveal the pedagogical approaches, the specific instructional/learning activities, the technologies utilized and the overall framework for developing blended learning experiences.